Analiza poslovanja slovenske lesne panoge - Kropivšek, Jože (Les (Ljubljana), 2017)
The sector, which plays a strategically important role within the economy, is subjected to numerous economic measures that influence its long-term development. The purpose of this article is to analyse the situation in the Slovenian wood industry and evaluate its position in the economy and its development in the last few years. The results of qualitative and quantitative analyses show improvements in a number of key financial indicators in the sector, as well as its qualitative situation in the context of Slovenia%s overall economic and political scene. Turnover, number of employees, added value and some other key performance indicators have all increased recently. The growth of the sector has a positive effect on public perceptions of it, which then influences the developmental and investment potential of the industry, with positive impacts on employment and further investment in research. Such growth also helps companies enhance their networking both inside and outside the sector. Overall, companies should continue with their efforts to introduce the latest production and information technologies as part of the transition to an Industry 4.0 model, while also updating of their business models
Keywords: analiza poslovanja; financial indicators; finančni kazalniki; kompozit; lesarstvo; sector analysis; Slovenia; Slovenija; SWOT; wood-industry